THE EFFECT OF COAGULATION BATH ON THE CELLULOSE ACETATE POLYMERIC MEMBRANE - KAH WAI, EYU (IRC, 2017)
Polymeric membranes were leading in the industry of separation due to their advantages in term of performance and economic aspect. However, there were limitations of the polymeric membrane for gas separation processes such as the trade-off between the membrane permeability and selectivity of polymeric membrane. Hence, this project investigated the preparation and characterization of cellulose acetate (CA) polymer membrane. The membranes were fabricated by dry/wet phase inversion method. During this phase, there were three major parameters of coagulation bath to be studied which were the coagulation bath temperature (CBT) in the range of 30-50 °C, pH of coagulation bath in the range of 5-9 and composition of ethanol (0-20%) in coagulation bath. The effects of these varying parameters on the CA membrane properties were studied in this research. The crystallinity, surface morphology, thickness, particle size and thermal stability of CA membrane were investigated through membrane characterization techniques like Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FT-IR), Thermo-gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD) and Particle Size Analyser. TGA studied the degradation of all of the CA membranes prepared with different parameters of coagulation bath which was occurred in three steps: (i) evaporation of water content (ii) main thermal decomposition of CA (iii) carbonization of degraded residues with different decomposition temperatures of CA membranes ranging from 269.51 °C to 302.66 °C. Besides, DSC studied the thermal stability of all the membranes prepared including the glass transition temperature (190 °C), melting temperature (220 °C) and the fusion enthalpies. From PSA, the surface weighted mean diameter of CA was 112.626 μm, volume-weighted mean diameter of CA was 289.233 μm and the mean particle size diameter of CA was 259.928 μm. In addition, the FTIR spectra of all of the CA membranes showed similar patterns. Finally, SEM studied the different surface morphologies of CA prepared in different parameters of coagulation bath.